2020
DOI: 10.2355/isijinternational.isijint-2019-589
|View full text |Cite
|
Sign up to set email alerts
|

Reaction between CO<sub>2</sub>–O<sub>2</sub> Mixture Gas and Fe–C Melts by Isotope Tracing Method

Abstract: In order to clarify the role of O 2 and CO 2 which are applied to steelmaking, the isotope tracing method has been used to study the decarburization reactions between CO 2-O 2 mixed gas and Fe-C melts containing different carbon contents at 1 873 K. When the mixture of two isotope gases of 18 O 2 and 13 CO 2 reacts with melts, the isotopic composition of the reacted gas is monitored online by a mass spectrometer. According to the change of isotopic gas composition, the ratio of various reactions and the decarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…As for CO, there were two sources and one destination: generation by O 2 and [C], generation by CO 2 and [C], and the consumption of post combustion, which flowrates were assumed as Q z1 , Q z2 and Q z3 (mL(STP)•min -1 ) respectively. Moreover, the flow monitoring converts different gases based on gas viscosity [32]- [34]) , when CO 2 -based gas, 1 mL(STP)•min −1 O 2 , CO and Ar (SCCM) can be converted into 1.38 mL(STP)•min -1 ,1.20 mL(STP)•min -1 and 1.50 mL•min -1 CO 2 (SCCM), respectively. Therefore, the relationship based on the chemical reaction can be established simultaneously:…”
Section: The Principle Of Isotope Tracing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for CO, there were two sources and one destination: generation by O 2 and [C], generation by CO 2 and [C], and the consumption of post combustion, which flowrates were assumed as Q z1 , Q z2 and Q z3 (mL(STP)•min -1 ) respectively. Moreover, the flow monitoring converts different gases based on gas viscosity [32]- [34]) , when CO 2 -based gas, 1 mL(STP)•min −1 O 2 , CO and Ar (SCCM) can be converted into 1.38 mL(STP)•min -1 ,1.20 mL(STP)•min -1 and 1.50 mL•min -1 CO 2 (SCCM), respectively. Therefore, the relationship based on the chemical reaction can be established simultaneously:…”
Section: The Principle Of Isotope Tracing Methodsmentioning
confidence: 99%
“…The experimental apparatus was followed by the previous work [32]) . An alumina tube containing 25.00±0.01 g of a metal sample heated in a high-temperature vertical tube furnace with argon (Ar, Purity ≥ 99.999%).…”
Section: Experimental Details 21 Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the experiment, the reaction rate constant is estimated to be 1.5 × 10 − 5 mol•cm − 2 s − 1 at 1 600°C. Fan et al 53) studied the decarburization rate of Fe-C melts with a CO 2 -O 2 mixture by employing the isotope tracing technique. Their results indicate that the utilization rate of CO 2 exceeds 97%.…”
Section: Isotope Exchange Techniquementioning
confidence: 99%
“…6 Emission reduction and recycling of carbon dioxide in metallurgical processes have become more prominent and urgent. 7 In recent years, Zhu and co-workers [7][8][9] conducted a series of industrial experiments to study the CO 2 -O 2 mixed injection (COMI) process in the basic oxygen furnace (BOF). It was found that the dust generation rate of the COMI process was reduced by about 19.3%, and the dephosphorization rate was increased by 7.53-13.39%, compared with the conventional steelmaking process.…”
Section: Introductionmentioning
confidence: 99%